ACUTE MYOCARDIAL INFARCTION MASKING THYROTOXICOSIS IN PREGNANCY - MM, Nur Hidayah; WA, Sini Sanaa; MA, Masliza Hanuni (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Myocardial infarction in pregnancy is a rare incidence with cases ranging from 1 to 10 per 100 000 deliveries and only 2% are caused by vasospasm. A direct explanation or mechanism as to how hyperthyroidism can cause acute myocardial infarction is not fully understood, but a few mechanisms has been proposed and one of it is related to coronary artery vasospasm. CASE We report a case of a 28-year-old female with twin pregnancy at 11 weeks of gestation, presenting with severe left sided chest pain radiating to left upper limb. She had no previous thyroid disease and was clinically euthyroid. Blood pressure was 119/76 with pulse rate 100 beats per minute at presentation. Electrocardiography done showed ST elevation at inferior lead with lateral involvement. CKMB done was 724 u/L (< 24). Thrombolysis achieved no resolution of ST elevation post thrombolysis. Echocardiography shows basal posterior dyskinesia. Coronary angiography revealed normal coronary arteries. Thyroid function test (TFT) reveals TSH <0.005 mIU/L (0.4 – 4.0), free T4 (fT4) 58.31 pmol/L (7.8 – 14.4) and T3 16.73 pmol/L. TSH-receptor antibody <0.80 iu/L (<1.75). The liver enzymes were deranged with AST 833 u/L (<75) and ALT 185 u/L (<45). She was diagnosed as Myocardial Infarction with Non-Obstructive Coronary Arteries (MINOCA) with thyroxicosis. She was started on Lugol’s solution in the ward. Prior to discharge, her repeat TSH was <0.005 mIU/L and fT4 14 pmol/L after 5 days of Lugol’s. She was discharged with Carbimazole 15 mg daily which was stopped at 19 weeks as TFTs normalized. CONCLUSION Thyrotoxicosis can have a variety of presentations and AMI is one manifestation. It should be considered in a patient presenting with acute MI who do not fit the usual demography and has no obvious risk factors for coronary artery disease.